Behavior Patterns of Betch Fish (Betta sp.) Towards Different Lamp Light Colors - Prilda Rizky Hasibuan; Sri Jayanthi; Siti Rahmawati Sitorus; Rizka Fadillah Br Siregar; Agnes Lidya Syahtari Purba; Silvia Wardania; Ella Fizh Sahrin; Sahna Maulana Sitakar; Gita Prilien Aibekob; Mely Supiani; Dwi Putri Oktaviani Sinabariba (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Betta fish (Betta sp.) is a type of ornamental fish that has unique characteristics compared to other ornamental fish. This research was carried out in November 2023 with the aim of finding out the behavioral patterns of Betta fish when exposed to different types of light. This research used a quantitative method with a (RAL). The results of the research showed that there were changes in behavior in Betta fish (Betta sp.) that had been given different colored lights. The reason why fish are attracted to light is, among other things, because fish have positive phototaxis properties which cause fish to be stimulated and attracted to gather at light sources. In this research, it can be seen that the movement of betta fish moves away from the light source, because the light coming out of the lamp will become hot if it is turned on for too long. If this goes on for a long time, it is feared that the fish will become bored and also experience stress.